On farm soil health assessment across seven sub‐tropical cover crop management systems - Tanjila Jesmin; Naba R. Amgain; Abul Rabbany; Noel Manirakiza; Jay Capasso; Kevin Korus; Jehangir H. Bhadha (Agrosystems, Geosciences & Environment)
Abstract The integration of cover cropping in conventional farming systems has shown positive impacts on soil health enhancement. In Florida, where concerns persist about low productivity in mineral soils and significant carbon loss from organic soils, farmers are increasingly adopting cover crops in their routines. This collaborative study aimed to evaluate the immediate effects of cover cropping, comprehend the connections between soil health indicators, and measure quality indices for both mineral and organic soils. Across Florida, we conducted a comprehensive on‐farm study, gathering 272 samples from both mineral and organic surface soils, which were treated with winter or summer cover cropping, rice cultivation, and fallow or flooded fallow. After analyzing 12 health indicators, we employed statistical methods such as mean comparison, non‐parametric correlation, and regression for both pre‐ and post‐cover cropping periods. A modified Comprehensive Assessment of Soil Health scoring system was utilized to assess the quality indices of both soil types. Notably, cover cropping enhanced cation exchange capacity (CEC) and soil protein (SP) in organic soil while preserving an unchanged active carbon (AC) pool. In mineral soils, such practices improved CEC, organic matter, maximum water holding capacity, SP, and total Kjeldahl nitrogen while reducing bulk density and AC. Following cover cropping, correlations among indicators became more pronounced, emphasizing the intricate relationships among soil properties and essential nutrients. Despite this alteration, the health indices did not change in both soils after cover cropping. The study's confined duration, limited to a single cover crop season, may account for the observed impact.